Overcoming the Challenges of Epilepsy in Nepal- From Grassroots to Advanced level - Gajuryal, Sharad Hari; Maharjan, Shreejana; Maharjan, Shreejana; Iida, Koji; Pant, Basant (Annapurna Journal of Health Sciences, 2023)
Epilepsy is considered to be one of the common neurological disease with a high public health concern in recent years. The burden of epilepsy is also high affecting the patients and their care givers physically, mentally as well as socio economically. This burden seems very high in low- and middle –income countries with high rate of treatment gap resulting in higher number of morbidity and mortality. There are various challenges in low-middle income countries to overcome the treatment gap. Sustained and coordinated action prioritizing epilepsy from the rural setting to the advance setting can help in tackling the challenges. This article focuses on the challenges of epilepsy treatment in low-middle income country like Nepal and discusses the ways forward to overcome it.